Rapid Hydropower Potential Assessment for Remote Area by using Global Data. Issue 1 (July 2021) - Farid, Mohammad; Rizaldi, Akbar; Prahitna, Aqsha; Badri Kusuma, Muhammad Syahril; Kuntoro, Arno Adi; Kardhana, Hadi
Abstract: Indonesia currently is facing an energy crisis due to depletion of oil reserves and rapid growth in conventional energy consumption. The declining fossil energy potential especially oil and gas has encouraged the government to put new renewable energy (NRE) as the main priority to maintain energy security for national supply in the future. NRE in Indonesia is generated from bioenergy power, hydro power, solar power, tidal power, wind power, and potential. However, NRE utilization in Indonesia is only about 11% from the total potential. This study assesses the hydropower production capacity of Ayung River Basin, the biggest Basin in Province of Bali. The assessment is carried out by utilizing global data that can be easily accessed. It was found that there are several potential mini-hydropower locations around the Ayung River Basin, with the biggest potential is around 2 MW.